Does Incapacitation Reduce Crime? - Piquero, Alex R. (Journal of quantitative criminology, 2007)
Questions and answers about incapacitation abound in all discussions about criminal justice policy. They are among the most pressing of all research issues, yet estimates about the incapacitation effect on crime vary considerably, and most are based on very old and incomplete estimates of the longitudinal pattern of criminal careers. This paper provides an overview of the incapacitation issue, highlights information on recent estimates of criminal careers that are useful to the incapacitation model, and outlines an ambitious research agenda for continued and expanded work on incapacitation and crime that centers on developing better estimates of the characteristics of criminal careers and their relevance to policy choices.